2023
DOI: 10.3390/microorganisms11071648
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum LBUX23 Isolated from Feces of a Newborn; Potential Probiotic Properties and Genomic Characterization

Pedro A. Reyes-Castillo,
Raquel González-Vázquez,
Edgar Torres-Maravilla
et al.

Abstract: Bifidobacterium longum is considered a microorganism with probiotic potential, which has been extensively studied, but these probiotic effects are strain dependent. This work aims to characterize the probiotic potential, based on the biochemical and genomic functionality, of B. longum LBUX23, isolated from neonates’ feces. B. longum LBUX23 contains one circular genome of 2,287,838 bp with a G+C content of 60.05%, no plasmids, no CRISPR-Cas operon, possesses 56 tRNAs, 9 rRNAs, 1 tmRNA and 1776 coding sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that many Bifidobacterium and Lactobacillus strains are known to produce BSH. 31,32…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that many Bifidobacterium and Lactobacillus strains are known to produce BSH. 31,32…”
Section: Resultsmentioning
confidence: 99%
“…Survival in the low-pH environment of the gut is also important as a technological property, especially in the food sector, considering that yogurt and fermented milks are the most used carriers for probiotics administration. Despite the importance of efflux pumps and changes in the cell envelope [270][271][272], genomic analysis supported the identification of argC, argH, and dapA, as acid-tolerance-associated genes, which may play an essential role in high acid tolerance [273,274] in the probiotic Bifidobacterium longum NCIM 5672; (iii) antagonism against pathogens through production of antimicrobial compounds and short-chain lactic and fatty acids [275] with anti-inflammatory properties, gut barrier protection, and immunomodulation [276]. The bacteriocins are proteinaceous compounds that are able to damage the outer membrane of pathogenic bacteria, act as a protective barrier against biofilm development and have also been linked to probiotic immunomodulatory, anticancer, antioxidant, antibacterial, and cholesterol-lowering activities [277].…”
Section: Genomics and Transcriptomicsmentioning
confidence: 99%